Building Roof Covering Materials for Residential and Commercial: Comparison and Best Choices - Artha, Hufa Weno; Syah, Nurhasan; Putri, Prima Yane (Universitas Negeri Padang, 2024)
Choosing the right roofing material is an important aspect of building design and construction. Both residential and commercial buildings have roof-related needs. But basically, the selection of roofing materials is not only for protection from but also based on energy efficiency, aesthetics, and longevity of the building. In addition, the design of roof shape selection must be done carefully because the wrong selection can cause rainwater seepage or leakage on the roof and high repair costs. This research aims to explore by comparing the characteristics of roof covering materials and provide the best choice based on needs. The research method used is a qualitative research method with the stages carried out, namely data collection techniques, sample determination, data analysis and research conclusions. Based on the analysis, it is concluded that for residential houses, tile roofs and concrete deck roofs are the best choice because they offer an optimal combination of aesthetics, durability, energy efficiency, and cost that is suitable for the Indonesian climate. While for commercial buildings, metal tile roof is an excellent choice due to its durability, energy efficiency, and modern aesthetics that suit the needs of commercial buildings.